2020
DOI: 10.3390/cells9071704
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of ACE/ACE2 Pathways: The Rationale for the Use of Renin-Angiotensin System Inhibitors in COVID-19 Patients

Abstract: The article describes the rationale for inhibition of the renin-angiotensin system (RAS) pathways as specific targets in patients infected by SARS-CoV-2 in order to prevent positive feedback-loop mechanisms. Based purely on experimental studies in which RAS pathway inhibitors were administered in vivo to humans/rodents, a reasonable hypothesis of using inhibitors that block both ACE and ACE2 zinc metalloproteases and their downstream pathways in COVID-19 patients will be proposed. In particular, metal (zinc) c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(142 citation statements)
references
References 190 publications
(538 reference statements)
2
139
0
1
Order By: Relevance
“…At present, despite numerous investments and scientific reports, hyperimmune plasma (a hundred-year-old practice) is the only SARS-CoV-2-specific therapy that is routinely used in clinical practice, although a few neutralising mAbs specific to SARS-CoV-2 antigens are now in clinical trials [1,2]. For severely affected patients not responding to chloroquine, antiviral, anti-inflammatory and anticoagulation combination therapies, hyperimmune plasma represents the last option despite some drawbacks [3][4][5]. High expectations and hopes are placed on SARS-CoV-2 vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, despite numerous investments and scientific reports, hyperimmune plasma (a hundred-year-old practice) is the only SARS-CoV-2-specific therapy that is routinely used in clinical practice, although a few neutralising mAbs specific to SARS-CoV-2 antigens are now in clinical trials [1,2]. For severely affected patients not responding to chloroquine, antiviral, anti-inflammatory and anticoagulation combination therapies, hyperimmune plasma represents the last option despite some drawbacks [3][4][5]. High expectations and hopes are placed on SARS-CoV-2 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Whether global herd immunity by vaccination will be hardly achievable, yearly SARS-CoV-2 vaccinations (as for influenza) of people at risk of severe forms will be instead feasible to urgently protect this (minority) part of the population. In this regard, other authors and I have already highlighted that individuals with low probability to survive to SARS-CoV-2 infection are usually elderly with comorbidities correlating with pre-existing high levels of circulating ACE2 concentration/activity that could be used as a prognostic marker [3,[7][8][9]. Priority for vaccination should be given to the more vulnerable group of the population (possibly individuals with high systemic ACE2 activity) for which the risk/benefit balance is more favourable.…”
Section: Introductionmentioning
confidence: 99%
“…All the mentioned above mechanisms involved in MF in DDC are similar to those occurring in more studied models, such as myocardial infarct or hypertension, where the RAAS has been extensively shown to modulate the actions of most of the remaining pro-fibrotic and pro-inflammatory factors mentioned above, mainly through its primary effector molecule ANG2 and the ANG2 type 1 receptor (AT1R) [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Overview Of the Fibrotic Process In Ddcmentioning
confidence: 99%
“…Interestingly, both in vivo studies showed similar reversibility of hypercapnia-induced defects in antiviral and antibacterial immunity [ 25 , 29 ]. There have been several reports suggesting that hypercapnia activates the renin-angiotensin system and angiotensin-converting enzyme 2 (ACE2) expression [ 116 , 117 , 118 ], which is identified as a receptor for the spike protein of SARS-CoV-2 and facilitating the viral entry into target cells [ 118 ]. It has not yet been reported that hypercapnia affects the pathogenesis of SARS-CoV-2 infection, but these findings in the studies of hypercapnia may also provide new insights into the understanding of the SARS-CoV-2 infection mechanisms.…”
Section: Detrimental Effects Of Hypercapnia In Asthmamentioning
confidence: 99%